Theoretical essays on trade policies, mergers and foreign direct investment - Nathananan, Montri. (2003)
This thesis is a collection of theoretical essays in the area of trade policies, mergers and foreign direct investment. We employ partial equilibrium analysis to investigate various issues concerning the above topic.